Harmonic analysis of traction power supply system: case study of Addis Ababa light rail transit - Shimelis Atli Assefa; Asegid Belay Kebede; Demissu Legese (IET Electrical Systems in Transportation)
Abstract Addis Ababa, the capital of Ethiopia, inaugurated the first electrified light rail transitsystem 4 years ago in September 2015, which makes it the first of its kind in sub‐Saharan and eastern African countries. The railway line has a total length of 34.25 km with 39 passenger stations and 19 traction substations. Currently, the performance of the traction power supply system degraded severely due to the existence of harmonics in the traction network. Realizing the above problem, the harmonic analysis of Addis Ababa light rail transit electrified power supply system is presented. The analysis is performed on one of the substations called ‘Lideta’ rectifier substation. To this end, mathematical modelling and analysis of the traction main components such as the catenary, the traction transformer, the traction rectifier and the load have been done. Finally, MATLAB simulation has been performed, and the result comes with a significant reduction in harmonic distortion, which is far below the 5% limits of IEEE standard.